Interleukin-6 Gene Promoter Region Polymorphism in Patients with Dilated Cardiomyopathy - Arooj, Sumbal; Khan, Muhammad; Raza, Ali (Cardiology and Cardiovascular Medicine, 2019)
Background: Dilated cardiomyopathy (DCM) is a primary myocardial disease characterized by left ventricular or biventricular dilatation and impaired myocardial contractility. IL-6 is a pro-inflammatory cytokine that has been found to play an important role in the pathogenesis of DCM. The present study endeavors to explore the association of IL-6 -174 G/C polymorphism in patients with dilated cardiomyopathy, in addition to several other contributing risk factors in Pakistani population. Method: The study population comprised of 76 patients (54 males and 22 Females) and 66 controls (47 males and 19 Females). Biochemical characteristics were analyzed to detect serum lipid profile. Genotyping was carried out by polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP). The data was analyzed for statistical significance using student t-test, chi-square analysis. Result: Comparison of wild type (GG) and (GC+CC) variant for IL-6 -174 G/C polymorphism showed that GC+CC was more common in patients’ group (20%) as compared to controls (4.5%). Similarly, significant association of variant allele C with DCM patients was found (OR = 4.708, 95% CI = 1.331-16.648, P = 0.0175). BMI was significantly higher among patients as compared to controls (P = 0.0004). The lipid profile of studied population showed significantly increased serum cholesterol (P < 0.0001), LDL-C levels (P < 0.0001) and HDL-C (P < 0.0001) in DCM patients as compared to controls. However, no significant difference was observed for TG and vLDL-C between patients and controls. Conclusion: Our findings indicated that IL-6 -174 G/C gene polymorphism may be associated with development of DCM.